Son to father reciprocity and encephalization in early humans - John M. Hartwick (Queen's University, Department of Economics, 2009)
Humans exhibit much more sharing of food harvested by prime-age hunter-gatherers with dependents relative to such sharing by lower-order primates. We investigate this behavior in a model in which a father provides generously to his dependent child-son in period t in the hope that this gesture will inspire his son to reciprocate in the next period when the father is in retirement. In our formulation fathers provide better when (a) they are smarter hunters (b) they have a higher probability of living to experience a retirement and (c) when they are more confident that their child-sons will indeed provide generously for them in their retirement. Better food provision by prime-age fathers is associated with brain-size expansion in our model.
Keywords: J10; J12; J22; 330; reciprocity; encephalization; intertemporal division of labor; Generationenbeziehungen; Austauschtheorie (Soziologie); Väter; Kinder; Theorie